Cities as places and topics of studies - Hočevar, Marjan (Urbani izziv, 2021)
In research articles, cities usually occur as topics (e.g., subjects or actors) or places of studies (e.g., sites, destinations, locations, or spaces). Investigation of more general patterns is rare because research usually focuses on individual cities. We use science mapping, based on Scopus data and Vosviewer visualization software, to examine city-related research across journals and disciplines (subject areas), and to assess how multiple city functions are reflected in journals. Comparable European Union capital cities (Berlin, Madrid, Rome, and Warsaw) serve as models. The patterns are remarkably similar regardless of the city. National and regional journals are the most common publication venues. Research takes place within three major disciplinary clusters: 1) the social sciences, and arts and humanities, 2) medicine, and 3) natural/technical sciences (environmental, earth and planetary, agricultural, and biological sciences). Medicine shows an early prevalence, and recently the social sciences have been strongly represented in these studies. Although the relationships are based on different journals, they are comparable for all cities and can be used to assess cities of similar size. This study was conducted just before the Covid-19 pandemic, and it can serve as a reference to identify research patterns before and after because the outbreak may bring about changes in future city-related research.
Keywords: bibliometrija; cities; mesta; raziskovalna področja; research fields; science mapping; visualization; vizualizacija; znanstveno kartiranje